Attenuation of the Effect of Salinity by Ascophyllum nodosum Extract on Growth Associated Traits of Mung Bean Cultivars [Vigna Radiata (L.) Wilczek] - SANGEETA KUMARI; KRISHAN SEHRAWAT; DEEPAK PHOGAT; POONAM MUNDLIA; RAVISH CHOUDHARY; ANITA R. SEHRAWAT (Seed Research, 2026)
Mung bean [Vigna radiata (L.)] is grown for its protein-rich edible seeds. Its productivity in the last few decades is stagnant because of biotic and abiotic constraints. Among the abiotic factors, salinity is of paramount importance as it severely affect the productivity of sensitive crops like legumes. Salinity has a deleterious effect on the growth associated traits at an early stage of the seedling. Brown alga, Ascophylum nodosum extract (ANE) impart stress tolerance in sensitive crops. Hence, four genotypes of Mung bean were screened to assessthe effect of different concentrations of NaCl and Ascophyllum nodosum extract (ANE) individually and in combinations on early seed vigor parameters. The germination process was evaluated daily up to seven days and observations like Percent Germination (PG), Germination Rate (GR), Germination Capacity (GC) and Germination speed (GS), Vigour Index (VI), Coefficient of Velocity of Germination (CVG), Seed Vigour Index (SVI), Standard germination (StG), Membrane Stability Index (MSI), Hypocotyl length (HL), Root length (RL) and secondary root number were recorded. All cultivars behaved differently. MH 215 was better for GC, VI, SVI, HL, RL and secondary root and MH 421 was superior for GS, StG, MSI. However, per cent germination and GR were better in MH125 and MH 318. It was concluded that a low concentration of ANE individually or in combinations with low salt ameliorated the effect of NaCl on growth attributes in Mung bean.